The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/slct.202200968
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Theoretical Study of Trifluoromethyl Derivatives of the IPR Isomer of C84 Fullerene, C84(11)(CF3)10,12,14

Abstract: C84 is the most abundant higher fullerene which is present in the arc‐discharge fullerene soot. Among 24 topologically possible Isolated‐Pentagon Rule isomers of C84, two major isomers, C84(22) and C84(23), and several minor ones have been identified experimentally. We report the synthesis, HPLC isolation, and synchrotron X‐ray structure elucidation of trifluoromethyl derivatives of the most abundant minor isomer of C84, C84(11)(CF3)10,12,14. The experimentally determined addition patterns are discussed in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The sublimate was dissolved in toluene and subjected to HPLC separation in toluene or toluene/ n ‐hexane mixtures. Some HPLC fractions isolated from the residue gave crystals of C 84 (11)(CF 3 ) 10,12,14 as reported previously [8] . Several fractions obtained via multi‐stage HPLC separation (including a recycling HPLC) of the sublimate afforded crystals by slow concentration or recrystallization from other solvents.…”
Section: Methodssupporting
confidence: 56%
See 4 more Smart Citations
“…The sublimate was dissolved in toluene and subjected to HPLC separation in toluene or toluene/ n ‐hexane mixtures. Some HPLC fractions isolated from the residue gave crystals of C 84 (11)(CF 3 ) 10,12,14 as reported previously [8] . Several fractions obtained via multi‐stage HPLC separation (including a recycling HPLC) of the sublimate afforded crystals by slow concentration or recrystallization from other solvents.…”
Section: Methodssupporting
confidence: 56%
“…The early stages of high‐temperature trifluoromethylation of C 84 (11) by consecutive addition of CF 3 groups up to C 84 (11)(CF 3 ) 12 have been considered in the previous report [8] . It was shown that both experimentally isolated C 84 (11)(CF 3 ) 10 ‐I and C 84 (11)(CF 3 ) 12 ‐I are the most stable isomers of a given composition.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations